Absence of a Relationship between Surface Conductivity and Electrochemical Rates: Redox-Active Monolayers on Si(211), Si(111), and Si(110) - Zhang, Song; Ferrie, Stuart; Lyu, Xin; Xia, Y.; Darwish, Nadim; Wang, Z.; Ciampi, Simone (AMER CHEMICAL SOC, 2021)
Optimizing the kinetics of an electrode reaction is central to the design of devices whose function spans from sensing to energy conversion. Electrode kinetics depends strongly on electrode surface properties, but the search for optimal materials is often a trial-and-error process. Recent research has revealed a pronounced facet-dependent electrical conductivity for silicon, implicitly suggesting that rarely used crystallographic cuts of this technologically relevant material had been entirely overlooked for the fabrication of electrodes. By first protecting silicon from anodic decomposition through Si-C-bound organic monolayers, conductive atomic force microscopy demonstrates that conductivity decreases in the order (211) ≫ (110) > (111). However, charge-transfer rates for a model electrochemical reaction are similar on all these crystal orientations. These findings reveal the absence of a relationship between surface conductivity and kinetics of a surface-confined redox reaction and expand the range of silicon crystallographic orientations viable as electrode materials.